2018
DOI: 10.1590/1807-1929/agriambi.v22n7p493-498
|View full text |Cite
|
Sign up to set email alerts
|

Salt balance in substrate cultivated with ‘Sunki’ mandarin x ‘Swingle’ citrumelo hybrids

Abstract: During initial plant development stage, an experiment was conducted to evaluate the balance of salts in the substrate used for the production of 10 hybrids from the cross between ‘Sunki’ mandarin (TSKC) and ‘Swingle’ citrumelo (CTSW), all with potential to be used as rootstock. ‘Rangpur Santa Cruz’ lime, ‘Sunki Tropical’ mandarin and the hybrid LVK (‘Volkamer’ lemon) x LCR (‘Rangpur’ lime) - 038 were included as controls, totaling 13 genotypes. Substrate samples were collected in the experiment conducted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The findings showed that the open field environment promoted higher concentration of Na + in the soil in all layers studied, especially when it was enriched with organic matter, which probably occurred due to greater volume of brackish water added in open field cultivation of noni and the addition of ions through mineralization of organic matter, as mentioned earlier. In this perspective, Almeida et al (2018), evaluating the effect of salinity in the cultivation substrate of hybrids of tangerine with citrumelo, found that the increase in salinity levels caused an increase in the Na + concentrations of the cultivation substrates, associating these increases with the use of the same salts used to prepare saline water in the present study (NaCl, CaCl 2 , and MgCl 2 in equivalent proportion of 7:2:1).…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…The findings showed that the open field environment promoted higher concentration of Na + in the soil in all layers studied, especially when it was enriched with organic matter, which probably occurred due to greater volume of brackish water added in open field cultivation of noni and the addition of ions through mineralization of organic matter, as mentioned earlier. In this perspective, Almeida et al (2018), evaluating the effect of salinity in the cultivation substrate of hybrids of tangerine with citrumelo, found that the increase in salinity levels caused an increase in the Na + concentrations of the cultivation substrates, associating these increases with the use of the same salts used to prepare saline water in the present study (NaCl, CaCl 2 , and MgCl 2 in equivalent proportion of 7:2:1).…”
Section: Resultsmentioning
confidence: 51%
“…In general, the open field environment promoted higher concentration of Ca 2+ in the soil, in all studied layers, especially in treatments with organic matter, which may have been a result of the addition of ions, both through mineralization of organic matter and the use of greater volume of brackish water in this environment (Almeida et al, 2018).…”
Section: Resultsmentioning
confidence: 83%
“…Regarding the differences observed between the genotypes, it is important to consider that when using saline water for irrigation the effects of salts on crops depend on the intensity and duration of saline stress and vary according to the species. In addition, genotypes of the same species may respond differently to the effects of salinity, which also manifest themselves differently at different stages of the crop cycle (Neves et al 2015;Almeida et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…If adequate soil, water, and plant management practices are not adopted, there will be economic and environmental damage to agricultural land. The lower growth and yield of several plant species exposed to salinity is due to osmotic effects, which reduce water absorption by plants, and the effects of specific ions, which can cause phytotoxicity and nutritional imbalance (Almeida et al 2018;Silva Sá et al 2018).…”
Section: Productive Characteristics Of Sunflower Genotypes Irrigated ...mentioning
confidence: 99%
“…Thus, selecting the appropriate substrate can be a difficult task that requires consideration of both physical and chemical features (ARCE; RIVERA, 2018). There are various substrate possibilities on the market, all of which are made from diverse material combinations; these substrates also have formulations and characteristics that are either known or unknown to the producers (FRANCO et al, 2007;ALMEIDA et al, 2018).…”
Section: Introductionmentioning
confidence: 99%